Value of biochemical markers in predicting outcome of COVID-19 infection in University Hospital, Alexandria, Egypt - Neveen Rashad Mostafa; Abeer Ahmed Mohamed Ali; Rehab Moustafa Ezzat; Mostafa Kamel Bakry; Roy Rillera Marzo (PAGEPress Publications, 2023)
This paper aims to examine the value of different biochemical markers in predicting the outcome of COVID-19 infection. A total of 140 patients with confirmed COVID-19 infection by polymerase chain reaction (PCR), different biochemical markers were tested, their relation to the outcome of the disease was monitored, and the most reliable tests were determined. The study found a significant correlation between all evaluated biochemical markers and severity of the disease, including C-reactive protein (CRP), D-dimer, alanine aminotransferase (ALT), Aspartate aminotransferase (AST), prothrombin time (PT), activated partial thromboplastin time (aPTT). In addition, ferritin, lactate dehydrogenase (LDH), procalcitonin (PCT) and Pro- Brain natriuretic peptide (proBNP) demonstrated highly sensitivity and specificity as well as significant prognostic performance. These markers were also independently significant in predicting mortality. Early assessment of biochemical markers in patients with COVID-19 can help clinicians in tailoring treatment and providing more intensive care to those with greater mortality risk. In particular, the assessment of ferritin, LDH, procalcitonin and proBNP can independently predict mortality.